Pengaruh Kepercayaan, Brand Image, Dan Nilai Pelanggan Terhadap Loyalitas Pelanggan Melalui Kepuasan Pelanggan Pada Layanan Asesmen PT XYZ Di DKI Jakarta - Bukti, Etika Noviyanti; Hardini, Resti (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
The decline in customer loyalty among users of assessment services at the PT XYZ in DKI Jakarta, particularly among state-owned enterprise (SOE) clients in 2023, serves as the backdrop for this research. This study aims to analyze the impact of trust, brand image, and customer value on customer loyalty, both directly and through customer satisfaction as a mediating variable. The method employed is a quantitative approach with a population of 120 clients utilizing assessment services in DKI Jakarta. The sampling techniques applied are non-probability sampling and purposive sampling. Data collection is conducted through surveys using a questionnaire as the research instrument. Data analysis is carried out using descriptive analysis and SmartPLS 3.0. The findings indicate that trust, brand image, and customer value have a positive and significant effect on customer loyalty. Additionally, customer satisfaction is shown to positively mediate the indirect effects of trust, brand image, and customer value on customer loyalty.